Quantifying soil losses and dust emissions by wind tunnel experiments in the cultivated steppe of Kazakhstan - Koza Moritz; Marzen Miriam; Funk Roger; Akshalov Kanat; Schmidt Gerd (E3S Web of Conferences)
Expanding agriculture and unsustainable farming practices in Central Asia’s steppes may increase the risk of wind erosion and severe dust emissions. However, empirical data from field experiments to assess a potential severe dust source is lacking. Therefore, a mobile wind tunnel was used in northern Kazakhstan to investigate the potential wind-induced soil loss and dust emissions under real field conditions common in agricultural practices. Field experiments were carried out on typical surfaces that act as dust sources: seedbeds as they occur after cultivation, in-field tracks, and dirt roads. Measurements were conducted by sediment collection of total eroded material and optical particle counting for particulate matter ≤30 µm. The results of the wind tunnel experiments show that the same soil can emit significantly different amounts of dust depending on the mechanical stress to which the soil was previously exposed. Soil loss and dust emissions increased from seedbeds to dirt roads due to the intensifying effect of pulverization by tires. In order to assess an area as a dust source or for emission inventories, the total emissions must be adjusted separately to these shares. Further insights of the field experiments will be presented at the conference.